Development of the electric automatic steering system for agricultural vehicles - An, Guangshun; Yu, Chong; Du, Juan; Yin, Xiang; Ni, Youliang; Jin, Chengqian (International Journal of Agricultural and Biological Engineering, 2024)
Automatic guidance of agricultural vehicles requires automatic execution of operation commands received from the navigation controller by using electronically controlled mechanisms for wheel steering, speed changing and work implementing. Automatic steering contributes as a prerequisite technique in automatic and semi-automatic agricultural navigation. This research aimed to develop an electric automatic steering system that was compact in its structure and integrated into original steering mechanism in a simply and convenient way for aftermarket modification. A brushless motor and reducer assembly was utilized to provide an adequate steering torque instead of manual maneuver. A rapid assembling approach was proposed by passing the steering shaft through the hollow output shaft. A digital proportional-integral-differential (PID) algorithm was implemented to calculate the rotation speeds and directions by comparing the desired angle and the actual angle, which was implemented in a printed circuit board with a microcontroller unit (MCU) and interface chips. An unmanned wheeled tractor was applied as test platform to integrate the newly developed electric automatic steering system. Tests were conducted to evaluate its performance in terms of stability and responsiveness. An autonomous navigation system guided the tractor along target paths in the field by sending steering commands to the electric automatic steering system. The results show that the steering angle error was less than 0.81° when desired steering angle was less than 10°. The lateral error difference was no more than 4.76 cm when repeating following the same target path, which indicated that the electric automatic steering system responded accurately and robustly to steering commands.Keywords: automatic steering, automatic navigation, agricultural vehiclesDOI: 10.25165/j.ijabe.20241701.8493Citation: An G S, Yu C, Du J, Yin X, Ni Y L, Jin C Q. Development of the electric automatic steering system for agricultural vehicles. Int J Agric & Biol Eng, 2024; 17(1): 209-214.